BIMBINGAN KONSELING MELALUI PENDEKATAN RATIONAL EMOTIVE BEHAVIORAL TERAPI DALAM MENGATASI PERILAKU KENAKALAN DI PONDOK PESANTREN - Indifatul Anikoh (AflahConsilia : Jurnal Bimbingan dan Konseling, 2022)
Teenagers are the next generation of the nation. However, Recently, the phenomenon of juvenile delinquency has become increasingly widespread, not only in urban areas but also in rural areas. Juvenile delinquency is behavior that deviates from social norms, religious norms and regulations that apply in society. One form of juvenile delinquency is a violation of the rules committed by teenagers, one of which is in Islamic boarding schools. The role of counseling is expected to help overcome the phenomenon of juvenile delinquency which is increasingly happening. This study aims to determine the role of counseling in tackling juvenile delinquency. By using library research methods. Methods of collecting data by reading books, articles, and journals. Guidance and counseling by using rational emotif behaviour therapy approach is effectife to give juvenile delinquency solution like indiscipliner case in Islamic boarding schools. Conselor helps a counselee detaility, holistic and focus In the process of giving therapy to changce behaviour and mindset of santri that do juvenil delinquency.